2020
DOI: 10.1212/nxi.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein altered expression and mislocalization in MS

Abstract: ObjectiveTo determine whether there are nuclear depletion and cellular mislocalization of RNA-binding proteins (RBPs) transactivation response DNA-binding protein of 43 kDa (TDP-43), fused in sarcoma (FUS), and polypyrimidine tract–binding protein (PTB) in MS, as is the case in amyotrophic lateral sclerosis (ALS) and oligodendrocytes infected with Theiler murine encephalomyelitis virus (TMEV), we examined MS lesions and in vitro cultured primary human brain–derived oligodendrocytes.MethodsNuclear depletion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Mislocalization of RBPs, including hnRNP A1, have been shown to be key pathologic features of neurologic diseases with a significant neurodegenerative component, such as ALS, FTLD, and MS ( Salapa et al, 2018 , 2020a ; Steinacker et al, 2019 ; Huang et al, 2020 ; Masaki et al, 2020 ). Several hypotheses explain a link between dysfunctional RBPs, and specifically their mislocalization, and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mislocalization of RBPs, including hnRNP A1, have been shown to be key pathologic features of neurologic diseases with a significant neurodegenerative component, such as ALS, FTLD, and MS ( Salapa et al, 2018 , 2020a ; Steinacker et al, 2019 ; Huang et al, 2020 ; Masaki et al, 2020 ). Several hypotheses explain a link between dysfunctional RBPs, and specifically their mislocalization, and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function of RBPs has been previously explored with another member of the hnRNP family of RBPs known as TAR-DNA-binding protein-43 (TDP-43), where nuclear clearance of TDP-43 has been shown to induce DNA double stranded break repair defects in ALS ( Mitra et al, 2019 ) and exacerbate neurodegeneration in an AD mouse model ( LaClair et al, 2016 ; Steinacker et al, 2019 ; Huang et al, 2020 ; Masaki et al, 2020 ). However, there are still critical gaps in our understanding of how loss-of-function of hnRNP A1 may impair neuronal functioning and contribute to neuronal degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of Th cells, including Th1 and Th17, release pro-inflammatory cytokines and contribute to CNS damage in MS, while anti-inflammatory phenotypes, such as Th2 cells, may play a more protective role during disease [20][21][22][23][24]. Several studies suggest that the immune system may contribute to RNA-binding protein (RBP) dysfunction, which is a feature of neurons from MS cortex and relevant MS models [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional RBPs play a role in neurodegeneration in other neurologic diseases and have only recently been implicated in the pathogenesis of MS and its models [26][27][28][30][31][32][33][34][35]. Neuronal RBP dysfunction is characterized by the mislocalization of the RBP from its nuclear homeostatic location to the cytoplasm and the formation of cytoplasmic stress granules (SGs), which can trigger cellular toxicity [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, altered RBP biology was identified in oligodendrocytes and neurons of MS cases. These data found altered expression of the RBPs TDP-43 and polypyrimidine tract-binding protein 1 and 2 (PTB1 / PTB2) in cortical demyelinated lesions [130]. Considering the importance of TDP-43 and PTB1/2 in oligodendrocyte viability and neuronal differentiation, respectively, researchers hypothesized RBP dysfunction might contribute to cortical lesion damage and neurodegeneration in MS [130].…”
Section: Evidence In Neuronsmentioning
confidence: 96%